Supporting and retaining Village Health Teams: an assessment of a community health worker program in two Ugandan districts - Daniel C. Mays; Edward J. O'Neil; Edison A. Mworozi; Benjamin J. Lough; Zachary J. Tabb; Ashlyn E. Whitlock; Edward M. Mutimba; Zohray M. Talib (BMC, 2017)
Abstract Background Uganda's national community health worker program involves volunteer Village Health Teams (VHTs) delivering basic health services and education. Evidence demonstrates their positive impact on health outcomes, particularly for Ugandans who would otherwise lack access to health services. Despite their impact, VHTs are not optimally supported and attrition is a growing problem. In this study, we examined the support needs and existing challenges of VHTs in two Ugandan districts and evaluated specific factors associated with long-term retention. We report on findings from a standardized survey of VHTs and exploratory interviews with key stakeholders and draw conclusions that inform efforts to strengthen and sustain community health care delivery in Uganda. Methods A mixed-methods approach was employed through a survey of 134 individual VHT members and semi-structured interviews with six key stakeholders. Descriptive and bivariate regression analysis of quantitative survey data was performed along with thematic analysis of qualitative data from surveys and interviews. In the regression analysis, the dependent variable is 10-year anticipated longevity among VHTs, which asked respondents if they anticipate continuing to volunteer as VHTs for at least 10 more years if their current situation remains unchanged. Results VHTs desire additional support primarily in the forms of money (e.g. transportation allowance) and material supplies (e.g. rubber boots). VHTs commonly report difficult working conditions and describe a lack of respect from their communities and other health workers. If their current situation remains unchanged, 57% of VHTs anticipate remaining in their posts for at least 10 years. Anticipated 10-year longevity was positively associated with stronger partnerships with local health center staff and greater ease in home visiting. Conclusions Supporting and retaining Uganda's VHTs would be enhanced by building stronger partnerships between VHTs and other health workers and regularly providing supplies and transportation allowances. Pursuing such measures would likely improve equity in access to healthcare for all Ugandans.